2022
DOI: 10.3389/fcimb.2021.727594
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms and Outcomes of Severe Pneumonia Caused by Chlamydia psittaci in Southwest China

Abstract: Here, we aimed to retrospectively analyze the clinical characteristics of 27 patients with severe pneumonia caused by Chlamydia psittaci between January 2019 and April 2021 in southwest China. To this end, we collected data on the exposure history, clinical symptoms, laboratory examination, imaging characteristics, evolution, etiology, treatment, and outcomes to suggest a better diagnosis and prevention system. Our results showed that a metagenomic next-generation sequencing test could provide early diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Metagenomic next-generation sequencing (mNGS) is a relatively new assay for the rapid and precise detection of pathogenic microorganisms (viral, bacterial, fungal, or parasitic) without bias through sequencing, which may assist in C. psittaci pneumonia diagnosis ( Langelier et al., 2018 ). The approach has been gradually applied in clinical practice in recent years, particularly for severe pneumonia in intensive-care unit (ICU) settings ( Yang et al., 2021 ), and has been demonstrated as an effective method for establishing clinical diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic next-generation sequencing (mNGS) is a relatively new assay for the rapid and precise detection of pathogenic microorganisms (viral, bacterial, fungal, or parasitic) without bias through sequencing, which may assist in C. psittaci pneumonia diagnosis ( Langelier et al., 2018 ). The approach has been gradually applied in clinical practice in recent years, particularly for severe pneumonia in intensive-care unit (ICU) settings ( Yang et al., 2021 ), and has been demonstrated as an effective method for establishing clinical diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of Chlamydia psittaci infection in foreign countries is less than 1% (Macfarlane JT & Macrae AD., 1983). However, two recent retrospective studies in our country showed that 4 out of 27 patients died due to secondary infection (Yang F, Li J, Qi B & et al, 2021), and 2 out of 13 patients died (Wu HH, Feng LF & Fang SY., 2021). In some other countries, psittacosis is a notifiable disease and must be reported within 48 hours (DE Boeck C, Dehollogne C, Dumont A & et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…A domestic study reviewed 27 patients with severe psittacosis pneumonia in Southwest China. Glucocorticoids were used when ARDS occurred (Yang F, Li J, Qi B & et al, 2021). There are also reports in China that the application of low-dose glucocorticoid therapy to patients with hepatitis B-related acute-on-chronic liver failure or severe infection prone to infection can significantly improve the liver function of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The primary symptoms include nonspecific respiratory symptoms, such as high fever, chills, fatigue, dry cough, and difficulty breathing, as well as symptoms of extrapulmonary organ involvement, including headache, muscle aches, and mental disturbances. Most patients have normal WBC counts and elevated creatine kinase and transaminases, and the primary manifestation of chest CT is consolidation ( Li et al., 2022 ; Yang et al., 2022a ; Yang et al., 2022b ). In this case, the lungs and extrapulmonary organs, including the liver, neuromuscular system, and haematological system, were involved, and the patient had obvious fatigue and loss of tendon reflexes, which were inconsistent with the symptoms of infection, poisoning, or myositis, thus raising the possibility of secondary central nervous system pathology.…”
Section: Discussionmentioning
confidence: 99%